DETERMINATIONS OF DIRECTIONS PERTAINING TO MODERNIZATION OF EARTH-DIGGING MACHINES - A. Ya. Kotlobai; A. A. Kotlobai; V. F. Tamelo (Наука и техника)
The paper considers main directions pertaining to earth-digging machinery modernization for combat engineering. Description of modernized drive hydraulic systems for technological equipment of track layers and trench and underground digging machine is given in the paper.